THE EXISTENCE OF ADAT LAW COMMUNITY IN PUBLIC-PRIVATE PARTNERSHIP - Karina Putri; Sartika Intaning Pradhani; Hendry Julian Noor (Faculty of Law, Universitas Sebelas Maret, 2020)
This paper aimed to elaborate the participation of Adat Law Community in Public-Private Partnership (PPP) to introduce new approach to replace compensation to more participative and collaborative scheme of infrastructure development in PPP. This article uses the normative legal research with the conceptual, statute, and case approach. This research show that releasing the land used for infrastructure development procurement will abolish the identity of the community. It have shown that failure in recognizing Adat Law Community as rightful party over their land neglects their right to entitle compensation. Furthermore, instead of economically compensating ulayat land of Adat Law Community used for infrastructure development, Adat Law Community’s participation shall be involved in infrastructure development on their land. The active participation of Adat Law Community can be exercised through placing the community as public entity in PPP. For comparison in China, the State does not pay according to market prices to farmers. However, it provides a compensation package that includes employment opportunities for farmers, housing compensation, compensation for crop loss, and / or granting a residence permit in urban areas. This make them eligible for their social welfare such as health insurance, pensions and / or retirement plans, access to high-quality schools and subsidized agricultural goods that were not previously available to farmers